Maximal strength, sprint and jump performance in elite kumite karatekas - Fahri Safa Cinarli; Onur Aydogdu; Yalcin Aydin; Gürkan Tokgöz; Abdulselam Kahraman; Ayşegül Beykumül; Caner Aygoren; Nurkan Yılmaz; Rodrigo Ramirez-Campillo (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Both maximal muscle strength and muscle power are independently important for karatekas. However, the relationship between strength and power in elite male kumite karatekas is under researched. This study aimed to determine the relationship between back-leg-chest (BLC) isometric muscle strength with sprint and jump variables in elite male karatekas. Methods Male elite/international level (tier 4) kumite karatekas (n = 14; age, 20.79 ± 1.67 year; height, 1.77 ± 0.06 m; weight, 72.21 ± 5.20 kg) were recruited. BLC strength, sprint and jump values were measured with a dynamometer, a photocell, and an application, respectively. Pearson correlation (trivial r < 0.1; small r < 0.3; moderate r < 0.5; large r < 0.7; very large r < 0.9; nearly perfect/perfect r ≥ 0.9) and linear regression analyses were performed to determine the relationship and shared variance between BLC strength, sprint, and jump performance. Results There were large to very large correlations between BLC strength and sprint time (r = − 0.930, p < 0.01), velocity (r = 0.918; p < 0.01), acceleration (r = 0.913; p < 0.01) and running momentum (r = 0.721; p < 0.01). Additionally, BLC strength correlated with jump height (moderate, r = 0.550, p < 0.05), peak anaerobic power (moderate, r = 0.672, p < 0.01) and power to body mass ratio (moderate, r = 0.545, p < 0.05). BLC strength and sprint variables showed an r 2 = 0.52–0.86 (p < 0.01), while BLC strength and jump variables showed an r 2 = 0.29–0.45 (p < 0.05). Conclusions BLC strength is related to jump and sprint performance in male elite karate athletes. This relationship underscores the importance of including strength training that targets BLC muscle strength in training programs for coaches and athletes.